Penerapan Metode Attribute Extraction pada Proses Perancangan Berbasis Komputer dan Penyusunan Bill of Materials Product: Kasus Perancangan Desain Tempat Tidur Pasien Rumah Sakit - Agus Mansur; Evin K. Prasetia Adi (Faculty of Industrial Technology Universitas Islam Indonesia, 2005)
During the design process, there still many industries use conventional system which can not completely accommodate the need of information. That’s why we need a system that can accommodate the necessity of designer and also end product user.Until now, what computer does in design process is only use as drawing tools. While the other vital functions like attribute geometric data and attribute non-geometric data is not use. This researcht is discussed about the design of patient’s bed in the hospital by using CAD, we hope that by using Attribute Extraction Method in CAD, we can get ergonomic design, Bill of Materials Poduct , Component of Draw Template, Supplier of the Basis Geometric Data and also to design animation’s product. So that, the experiment’s result can easier the machine process design and also the management supply of materials need.Keywords: product design, attribute extraction, bill of materials.